Teacher Professional Development Strategy Through Continuous Educational Innovation - Siti Fatimah Rahmawati; Abdullah Al-Rashid (Innovate Inovation Teaching And Learning, 2025)
This study aims to analyze strategies for teacher professional development through sustainable educational innovation in the digital era. The background of this research is rooted in the need for teachers to continuously adapt to technological developments, curriculum changes, and global dynamics that demand 21st-century competencies. The research employed a descriptive qualitative method by reviewing literature, observing practices, and analyzing outcomes of teacher community discussions. The findings indicate that sustainable educational innovation plays a crucial role in enhancing pedagogical skills, improving digital literacy, and fostering teachers' adaptive attitudes. Collaboration within learning communities has proven to be a key catalyst for collective innovation, while challenges such as limited infrastructure and digital literacy gaps open opportunities for more contextual strategies. This research emphasizes that teacher professional development requires not only technological integration but also collaboration, inclusive policies, and continuous commitment from all educational stakeholders.